Demons and Healing: The Reality of the Demonic Threat and the Doppelgänger in the Light of Anthroposophy: Demonology, Christology and Medicine - Thoresen, Are (Rudolf Steiner Press, 2020)
Intro -- Title Page -- Copyright Page -- Dedication -- Contents -- Foreword by Hans Kolstad -- Preface -- Introduction -- Chapter One Are Demons Real?-Personal Experiences -- Chapter Two How are Demons Created? Earth Radiation -- Chapter Three How to Stop or Prevent the Demonic Effects of Earth Radiation -- Chapter Four How Do We Free or Defend Ourselves from Demons? -- Addendum -- Spiritual beings and drugs -- Poltergeists -- Conclusion -- Afterword by Phil Rogers -- Acknowledgements.